Voluntary Disclosure and Investment* - Wen, Xiaoyan (Contemporary Accounting Research, 2013)
This paper examines the determinants and economic efficiency of corporate voluntary disclosure. The focus is on the trade-off for an individual firm when the costs and benefits of voluntary disclosure stem from the consequences of its investment decisions and the impact on its share price. Investment and voluntary disclosure decisions are intertwined. First, voluntary disclosure leads to more accurate pricing, which induces more efficient investment decisions. Second, the firm may affect the market pricing in its favor by strategically disclosing or withholding its private information. This opportunistic use of disclosure may cause the real investment to be distorted at the margin. My analysis shows that the efficiency of voluntary disclosure is influenced by both effects. Further, this paper investigates how the investment efficiency and the propensity for providing voluntary disclosure respond to various environmental variables. Two such key variables are the general economic outlook of the investment opportunity and the quality of firm private information.